Ultrafast hydrothermal assembly of nanocarbon microfibers in near-critical water for 3D microsupercapacitors. (June 2018) - Zhai, Shengli; Wei, Li; Karahan, H. Enis; Wang, Yanqing; Wang, Chaojun; Montoya, Alejandro; Shao, Qian; Wang, Xin; Chen, Yuan
Abstract: Translating the advantages of carbon nanomaterials into macroscopic energy storage devices is challenging because the desirable nanoscale properties often disappear during assembly processes. Here we describe a new nonequilibrium subcritical hydrothermal method capable of independently manipulating the temperature and pressure to create unique assembly conditions crossing the commonly used liquid-vapor boundary. Highly conductive and dense-packed yet ion-accessible nanocarbon microfibers can be obtained from graphene oxide sheets, single-walled carbon nanotubes, and a nitrogen-doping crosslinker under 20 min of hydrothermal assembly, 80% energy saving compared to standard hydrothermal methods, and one of the shortest time in the field of hydrothermal processing of carbon nanomaterials. Using those microfibers, we built microsupercapacitors that reach a high volumetric capacitance of 52 F cm −3, energy density of 7.1 mWh cm −3, and power density of 1645.7 mW cm −3, respectively. We further demonstrate the 3D integration of multiple fiber microsupercapacitors that reduces the device footprint by 75% while expanding the operational voltage and current window. This strategy is a promising tool for harmoniously assembling carbon nanostructures as energy storage components for various energy applications. Graphical abstract: A new hydrothermal system is capable of controlling the temperature and pressure of water independently to create unique hydrothermal assembly conditions for achieving ultrafast assembly of carbon nanomaterials into carbon architectures.Image 1